Elicitation of the in vitro Cultures of Selected Varieties of Vigna radiata L. With Zinc Oxide and Copper Oxide Nanoparticles for Enhanced Phytochemicals Production - Iqbal, Zunera; Javad, Sumera; Naz, Shagufta; Shah, Anis Ali; Shah, Adnan Noor; Paray, Bilal Ahmad; Gulnaz, Aneela; Abdelsalam, Nader R. (Frontiers in Plant Science, 2022)
This study was conducted to develop a protocol for in vitro shoot multiplication and callus induction of various mung bean varieties to get enhanced phytochemicals’ content. For shoots multiplication, two explants (shoot tips and nodal tips) of 3 varieties of Mung bean (Mung NCM-13, MgAT-7, and MgAT-4) from in vitro and in vivo sources were cultured on MS medium supplemented with different concentrations and combinations of BAP and IBA (0, 0.25, 0.50, 1.0, 1.50, 2.0, 2.50, and 3.0 mg/L separately). Leaf explants were cultured for callus development and medium used for callus induction included MS+ 2,4-D (1-3mg/L) along with BAP and NAA (0, 0.5 and 1.0 mg/L individually and in combinations). Thereafter, optimized callus cultures of three varieties were supplemented with zinc oxide and copper oxide nanoparticles (nanoelicitors) and these cultures were tested for phenolic and glycoside content. Results showed that in vitro explants responded better as compared to in vivo explants. Shoot tip were also better explants for mug beans as compared to nodal explants for given treatments. All three varieties showed the optimized results in the MS medium supplemented with BAP 1 mg/L while roots were produced only in cultures fortified with IBA 1mg/L. Immature leaf explants performed best in callus induction (90.0% and 80%) in MS supplemented with 3mg/L 2,4-D. Maximum phenolics (101.4µg eq. of gallic acid) were obtained from callus cultures of variety 2 of mung bean from MS + 2,4-D 3 mg/L. Whereas maximum glycosides were obtained from variety 3 of mung bean from MS + 2,4-D 3 mg/L. Furthermore, addition of zinc oxide and copper oxide nanoparticles to the callus culture medium significantly enhanced the phenolic content (26, 25.6 and 22.7% respectively) and glycosidic content (50, 37.5 and 25% respectively) of all the three varieties of mung bean used. It is suggested that by using the above mentioned protocols, multiple mung bean plants and callus cultures can be regenerated in future for enhanced production of phenolics and glycosides.